2018
DOI: 10.1021/acssuschemeng.8b04858
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Design of Covalent Organic Framework Membranes for CO2/CH4 Separation

Abstract: Membrane based CO 2 /CH 4 separation is an effective and energy saving way for highly demanded natural gas upgrading. Herein, high-throughput computational screening of covalent organic frameworks (COFs) for CO 2 /CH 4 membrane separation is realized by using the 298 COF structures in CoRE COF database. Based on the study of structure−performance relationships, structural features of the outperformed COFs were identified and classified, followed by the structural design by decorating 11 CoRE COFs with 10 kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 62 publications
2
85
0
Order By: Relevance
“…We used the third version of the CoRE COF database which consists of 309 COFs. 47 First, structural features such as pore-limiting diameter (PLD), the largest cavity diameter (LCD), accessible surface area ( S acc ), density (ρ), and porosity (ϕ) of materials were estimated using Zeo++ software (version 0.3). 56 S acc was calculated using a probe that has the same kinetic diameter as the N 2 molecule (3.64 Å), and we eliminated the COFs with null accessible surface area.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the third version of the CoRE COF database which consists of 309 COFs. 47 First, structural features such as pore-limiting diameter (PLD), the largest cavity diameter (LCD), accessible surface area ( S acc ), density (ρ), and porosity (ϕ) of materials were estimated using Zeo++ software (version 0.3). 56 S acc was calculated using a probe that has the same kinetic diameter as the N 2 molecule (3.64 Å), and we eliminated the COFs with null accessible surface area.…”
Section: Computational Detailsmentioning
confidence: 99%
“… 49 Computational screening of 187 CoRE COFs for adsorption-based noble gas separations under PSA and VSA conditions revealed that COFs can have high adsorption selectivities for Kr/Ar, Xe/Kr, and Rn/Xe and high working capacities for Kr and Xe. 45 A total of 298 CoRE COFs were investigated for CO 2 /CH 4 separation, 47 and it was found that −F and −Cl functional groups increased the membrane selectivities up to 2 orders of magnitude and carried several COF membranes over Robeson’s upper bound 17 which was defined for polymeric membranes. A total of 295 CoRE COFs were recently screened for CO 2 /N 2 separation, and it was concluded that many COF adsorbents can compete with MOFs in CO 2 capture from flue gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative to develop novel materials with orders of magnitude enhanced permeability while maintaining such selectivity for economically processing large‐scale CO 2 /CH 4 and CO 2 /N 2 separation . Molecular‐sieving membrane materials including inorganic and organic frameworks, such as zeolite, metal organic frameworks, and covalent organic frameworks, can achieve both high permeability and selectivity, but are challenging to be fabricated at large scale . Polymers of intrinsic microporosity (PIMs) and inherently microporous polyimides with rigid and contorted aromatic structures are recently designed and have high permeability (e.g., P CO2 ~4,000 Barrer), but relatively low selectivity compared with commercial membranes (cellulose acetate, polymides, polycarbonates, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…They predicted that a large number of MMMs yields a cost of carbon capture <$50 per tonne of CO 2 removed. Yan et al . recently performed high‐throughput computational screening of covalent organic frameworks (COFs) for CO 2 /CH 4 separation, and three well‐performed COFs identified from their computational screening were examined as fillers in MMMs composed of four different polymers.…”
Section: Introductionmentioning
confidence: 99%